Letter: intestinal inflammation, COVID‐19 and gastrointestinal ACE2—exploring RAS inhibitors. Issue 3 (3rd June 2020) - Garg, Mayur; Royce, Simon G.; Lubel, John S.
Abstract : LINKED CONTENT This article is linked to Taxonera et al papers. To view these articles, visit https://doi.org/10.1111/apt.15804 and https://doi.org/10.1111/apt.15893 .